The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1002/tesq.276
|View full text |Cite
|
Sign up to set email alerts
|

Making Pronunciation Visible: Gesture In Teaching Pronunciation

Abstract: The study examines the teacher and student gesture employed in teaching and learning suprasegmental features of second language (L2) pronunciation such as syllabification, word stress, and rhythm. It presents microanalysis of video-recorded classroom interactions occurring in a beginner-level reading class in an intensive English program at a U.S. university. Results indicate that the teacher employed gesture as an instructional tool to facilitate the students' identification and production of syllables, word … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(52 citation statements)
references
References 38 publications
1
44
0
Order By: Relevance
“…This consistent usage of materials appeared to sensitize students to its presence and develop students’ awareness and perception of such materials use in the classroom. Furthermore, L2 teachers should be aware of the roles of nonverbal resources (e.g., cut‐off, silence, gesture, and gaze) in thinking for teaching (Smotrova, ; van Compernolle & Smotrova, ) when they need to change material modes when reacting to students’ state of understanding. Excerpt 2 demonstrated how Teacher L effectively employed verbal and nonverbal resources in order to create space to think about appropriate materials in context.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This consistent usage of materials appeared to sensitize students to its presence and develop students’ awareness and perception of such materials use in the classroom. Furthermore, L2 teachers should be aware of the roles of nonverbal resources (e.g., cut‐off, silence, gesture, and gaze) in thinking for teaching (Smotrova, ; van Compernolle & Smotrova, ) when they need to change material modes when reacting to students’ state of understanding. Excerpt 2 demonstrated how Teacher L effectively employed verbal and nonverbal resources in order to create space to think about appropriate materials in context.…”
Section: Discussionmentioning
confidence: 99%
“…Note that “okay” marks a topic closing or shift (e.g., Beach, ) along with a cut‐off (“it‐”). Teacher L's turn (lines 47–52) displays the emerging process of her in‐flight pedagogical decision, associated with what Smotrova () and van Compernolle and Smotrova () called thinking for teaching . Thinking for teaching is defined as “teachers’ moment‐to‐moment instructional decisions in the classroom” (van Compernolle & Smotrova, , p. 2), which are often enacted through the gesture–speech interface.…”
Section: Analyzing Materials Moments In Multilingual Classroom Interacmentioning
confidence: 99%
“…In fact, empirical SLA embodiment/multimodality research has expanded considerably circa 2019—notable instances include studies conducted in the conversation analysis framework (e.g., Eskildsen & Markee, ; Hellermann, Thorne, & Haley, in press), sociocultural theory (e.g., Smotrova, ), and sociocognitive approaches to SLA (Atkinson et al., ; Atkinson & Shvidko, in press). But Block's larger point still holds: If language is fundamentally intertwined with other forms of embodied/multimodal meaning‐making, then it must be studied integratively.…”
Section: Discussionmentioning
confidence: 99%
“…Block concluded that "embodiment and multimodality are essential to ( …) understanding ( …) the kinds of processes studied by SLA researchers," and that it was "a line of research that has evolved, but ( …) only within the confines of what the linguistic-cognitive approach allows" (p. 73). 10 In fact, empirical SLA embodiment/ multimodality research has expanded considerably circa 2019-notable instances include studies conducted in the conversation analysis framework (e.g., Eskildsen & Markee, 2018;Hellermann, Thorne, & Haley, in press), sociocultural theory (e.g., Smotrova, 2017), and sociocognitive approaches to SLA (Atkinson et al, 2018;Atkinson & Shvidko, in press). But Block's larger point still holds: If language is fundamentally intertwined with other forms of embodied/ multimodal meaning-making, then it must be studied integratively.…”
Section: Embodiment and Multimodalitymentioning
confidence: 99%
“…SCT researchers van Compernolle and Smotrova () used CA techniques to study teachers’ and students’ gestures. As described above, SCT’s central principle is that SLA/T occurs via intentional and conscious artificial mediation, as captured in Smotrova’s () concept of intentional instructional gestures : “intentionally designed and consciously employed instructional tool[s] … intrinsically tied to instructional context and … unlikely to occur in everyday communication” (p. 83). Yet van Compernolle and Smotrova also described “rather spontaneous” gestures that, apparently because of their spontaneity, were effective pedagogical tools (p. 41).…”
Section: Evidence For Natural Pedagogymentioning
confidence: 99%